This preview shows page 1. Sign up to view the full content.
Unformatted text preview: k-1 committee members in ± n-1 k-1 ² . Combining the two we have n ± n-1 k-1 ² , possible choices. Part (d): Since all expressions count the same thing they must be equal and we have k ± n k ² = ( n-k + 1) ± n k-1 ² = n ± n-1 k-1 ² . Part (e): We have k ± n k ² = k n ! ( n-k )! k ! = n ! ( n-k )!( k-1)! = n !( n-k + 1) ( n-k + 1)!( k-1)! = ( n-k + 1) ± n k-1 ²...
View Full Document
This note was uploaded on 02/25/2011 for the course STAT 418 taught by Professor G.jogeshbabu during the Winter '08 term at Pennsylvania State University, University Park.
- Winter '08